Does Internet Gear up the Users Awareness of E-books? - a Survey - Saravanan, T.; Gopalakrishnan, S. (Journal of Information and Knowledge, 2011)
The aim of this study is to measure the users' awareness about the Internet and its resources particularly with their experience and e-books. Users' dependency of internet increases day by day as their requirements also raises in various aspects such as preparing lessons, assignments, research etc. Either academic or personal users are in need of modern technology to meet their requirements as present scenario offers the sophisticated opportunity along with the required infrastructure. The present study enables us to realize the modern users' experience levels as well as e-books awareness. Though many features are covered by Internet study includes the Digital Library related aspects only as this research falls under the discipline of LIS. Keeping this aspect in mind study has been focused on academic users' internet experience and various levels of awareness of e-books. The identified research questions in the present investigation are; does the user's Internet experience differ? Does the user's e-books awareness level differ? , Does the user's Internet experience influence them to gain awareness of e-books?.